Tropical fruit tree diversity: good practices for in situ and on-farm conservation - Sthapit, Bhuwon R.; Lamers, Hugo A.H.; Ramanatha Rao, V.; Bailey, Arwen (Routledge, 2016)
Farmers have developed a range of agricultural practices to sustainably use and maintain a wide diversity of crop species in many parts of the world. This book documents good practices innovated by farmers and collects key reviews on good practices from global experts, not only from the case study countries but also from Brazil, China and other parts of Asia and Latin America.